Konvergensi Konsep Retribusi Dan Rehabilitasi Dalam Filsafat Hukum Pidana Kontemporer Indonesia - Hikmah, Faidatul; Agustian, Rio Armanda (CREPIDO, 2023)
Abstract This research elaborates on the convergence between retribution and rehabilitation in Law No. 1 of 2023 concerning the New Indonesian Penal Code, which transforms the paradigm of criminal law in a holistic and integrative manner. The method used is juridical-philosophical, employing legislative and conceptual approaches to identify the transition process of the punishment concept in Indonesian criminal law. The research results indicate that the concept of retribution has evolved from the tradition of Continental European law to the post-colonial era in Indonesia. The retributive values of the Old Penal Code are no longer relevant to the cultural context of the Indonesian nation. The update of the Penal Code introduces rehabilitative values in a convergence, merging with the pre-existing retributive values to create an eclectic and ideal legal formulation. This aligns with the idea of balancing the values of Pancasila, which seeks proportional implementation between retributive and rehabilitative concepts in achieving substantive justice in Indonesia. Keywords: Retributive; Rehabilitative; Contemporary CriminalAbstrak Penelitian ini mengelaborasi konvergensi antara retribusi dan rehabilitasi dalam UU No. 1 Tahun 2023 tentang KUHP Baru Indonesia yang mentransformasikan paradigma hukum pidana secara holistik dan integratif. Metode yang digunakan adalah yuridis filosofis dengan pendekatan perundang-undangan dan konseptual untuk menemukan proses transisi konsep pemidanaan dalam hukum pidana di Indonesia. Hasil penelitian menunjukan bahwa konsep retribusi telah berkembang dari tradisi hukum Eropa Kontinental hingga pasca kolonialisme di Indonesia. Nilai-nilai retributif dari KUHP Lama tidak lagi relevasi dengan konteks kultural bangsa Indonesia.  Pembaruan KUHP mengintroduksi nilai-nilai rehabilitatif dalam sebuah konvergen, penggabungan dengan nilai-nilai retributif yang sudah ada sebelumnya untuk menghasilkan formulasi hukum yang eklektis dan ideal. Hal ini selaras dengan ide keseimbangan nilai Pancasila yang menghendaki implementasi proporsional antara konsep retributif dengan rehabilitatif dalam menciptakan keadilan yang substansial di Indonesia. Kata kunci: Retributif; Rehabilitatif; Pidana Kontemporer